2018
DOI: 10.1155/2018/7858094
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory Effect of a Polyphenol‐Enriched Fraction from Acalypha wilkesiana on Lipopolysaccharide‐Stimulated RAW 264.7 Macrophages and Acetaminophen‐Induced Liver Injury in Mice

Abstract: A polyphenol-enriched fraction (PEF) from Acalypha wilkesiana, whose leaves have been traditionally utilized for the treatment of diverse medical ailments, was investigated for the anti-inflammatory effect and molecular mechanisms by using lipopolysaccharide- (LPS-) stimulated RAW 264.7 macrophages and acetaminophen- (APAP-) induced liver injury mouse model. Results showed that PEF significantly attenuated LPS-induced nitric oxide (NO) and prostaglandin E2 (PGE2) production and suppressed the expression of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…The NFκB is then phosphorylated and converted to its active form. In the NFκB signaling pathway, MAPK regulates the activation of NFκB; the phosphorylation of MAPK induces the activation of NFκB followed by subsequent expression of inflammatory mediators and pro-inflammatory cytokines [ 10 , 22 ]. To investigate the effect of atraric acid on the MAPK/NFκB signaling pathway, LPS-stimulated RAW264.7 cells were treated with atraric acid to analyze the expression of the inflammatory mediators by Western blot.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The NFκB is then phosphorylated and converted to its active form. In the NFκB signaling pathway, MAPK regulates the activation of NFκB; the phosphorylation of MAPK induces the activation of NFκB followed by subsequent expression of inflammatory mediators and pro-inflammatory cytokines [ 10 , 22 ]. To investigate the effect of atraric acid on the MAPK/NFκB signaling pathway, LPS-stimulated RAW264.7 cells were treated with atraric acid to analyze the expression of the inflammatory mediators by Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…There is a great interest in the discovery of biologically active natural products due to their activities with relatively low toxicity as compared to other modalities such as synthetic chemicals [ 10 ]. Numerous studies have shown that natural products are developed as beneficial dietary supplements for health and therapeutic agents against disease [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 B). Redundant NO and PGE 2 , as inflammatory mediators, have been regarded as the main causes for acute inflammatory responses as well as chronic inflammatory diseases, such as osteoarthritis, rheumatoid arthritis, and inflammatory bowel disease [ 20 ]. In order to examine the effect of CLME on level of inflammatory mediators, we investigated NO and PGE 2 production in LPS-stimulated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%